2021
DOI: 10.3847/1538-3881/abd243
|View full text |Cite
|
Sign up to set email alerts
|

The McDonald Accelerating Stars Survey (MASS): White Dwarf Companions Accelerating the Sun-like Stars 12 Psc and HD 159062

Abstract: We present the discovery of a white dwarf companion to the G1 V star 12 Psc found as part of a Keck adaptive optics imaging survey of long-term accelerating stars from the McDonald Observatory Planet Search Program. Twenty years of precise radial-velocity monitoring of 12 Psc with the Tull Spectrograph at the Harlan J. Smith telescope reveals a moderate radial acceleration (≈10 m s −1 yr −1 ), which together with relative astrometry from Keck/NIRC2 and the astrometric acceleration between Hipparcos and Gaia DR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 103 publications
0
15
0
Order By: Relevance
“…Long orbits can often be constrained by comparing their motions measured at two widely separated moments (e.g., Brandt et al 2019;Currie et al 2020;Bowler et al 2021). These recent efforts use the Hipparcos-Gaia Catalog of Accelerations (HGCA; Brandt 2021), which has presented recalibrated proper motions of systems measured by the Hipparcos and Gaia missions, ∼30 years apart.…”
Section: Implications For the Known Literature Multiples Subsetmentioning
confidence: 99%
“…Long orbits can often be constrained by comparing their motions measured at two widely separated moments (e.g., Brandt et al 2019;Currie et al 2020;Bowler et al 2021). These recent efforts use the Hipparcos-Gaia Catalog of Accelerations (HGCA; Brandt 2021), which has presented recalibrated proper motions of systems measured by the Hipparcos and Gaia missions, ∼30 years apart.…”
Section: Implications For the Known Literature Multiples Subsetmentioning
confidence: 99%
“…The Hipparcos-Gaia Catalog of Accelerations (HGCA)-a combination of the exquisite astrometry from the Gaia mission and those from Hipparcos-provides a list of nearby stars whose proper-motion accelerations hint at the presence of massive, imageable companions on solar system scales (Brandt 2018;Gaia Collaboration et al 2018). Direct imaging surveys targeting these accelerating stars may have significantly higher yields than blind surveys and allow substantially improved characterization capabilities (e.g., Calissendorff & Janson 2018;Fontanive et al 2019;Currie et al 2020;Bowler et al 2021;Steiger et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Brandt et al (2019) extended this technique further by jointly fitting Hipparcos-Gaia astrometry with radial velocities and relative astrometry from direct imaging, and found that the orbits of massive companions can be precisely constrained even when the orbital periods are much longer than the observational duration. This method has been profitably applied to many further systems; Bowler et al (2021), for example, were able to extract precise orbital parameters and masses for two white dwarfs with orbital periods in excess of 200 yrs despite possessing no more than ∼ 30 yrs of observational data in both cases.…”
Section: Hip 94235 B: a 60 Au M-dwarf Companionmentioning
confidence: 99%